Development of method for manufacture of lassi fortified with moringa leaf - Mistry, Ekta M; Patel, Sunil M; Dharaiya, Chetan N; Patel, Komal N; Pinto, Suneeta V (Indian Journal of Dairy Science, 2017)
Lassi is among one of the most widely consumed fermented milk product in India. The present study was planned to develop a technology for manufacture of Moringa lassi containing Moringa leaf powder (MLP) as a value added ingredient. Moringa lassi was prepared from dahi made from standardized milk (4.5% fat/ 9.5% MSNF). Addition of MLP before fermentation resulted in a product with very harsh flavour and uneven body and texture with excessive whey separation. Therefore, MLP (dissolved in water and heated to 90 C for 1 min. for proper blending) was added directly into the lassi along with other flavouring ingredients viz. sugar, salt, spice mixture and stabilizer blend. Â The effects of varying level of total milk solids in lassi (6 to 10% w/w of lassi), acidity of dahi (0.6 to 0.9% LA) and level of MLP (0.5 to 1.0 % w/w of lassi) and their interactions on physico-chemical and sensory parameters of the product were assessed using Respose Surface Methodology. Based on surface responses, the optimal levels were: 8.0 % TMS in lassi, 0.77 % LA acidity of dahi and 0.7 % MLP. The standardized product was found to be an "excellent source of calcium" providing 23 % DV and â€œgood source of iron and Vitamin C and proteinâ€ providing 10 % and 11 % and 11 % DV respectively. These nutrients could be supplied by one serving size (250 g) of Moringa lassi. However the product was found to contain very low amount of fibre (0.2 % DV).